Pengembangan Media Puzzle Sugaka pada Pembelajaran Tematik Siswa Kelas II Sekolah Dasar - Nadia Nadia; Risdiana Andika Fatmawati; Muhammad Aqmal Nurcahyo (Jurnal Edukasi, 2023)
This study aims to determine the development of sugaka puzzle media for thematic learning for second grade students at SD Negeri 03 Sungai Raya. The research model used is development based on R&D (research and development). The validation results from all experts show that the development of puzzle media in thematic learning meets the valid criteria with the acquisition of a 100% proportion. The results of large-scale field trials with the acquisition of student responses to the Sugaka puzzle media obtained 93% results. Assessment of activity sheet 1 large-scale field test results obtained 98%. The posttest results obtained for all students scored (> 80), then the average score of all students was obtained on the posttest results of the initial field trials of students, namely 93 or "Very Good".